Promoting *scape : the iconic youth space in town - Dawidson, Diana (2008)
This project involved the promotion of *scape as the new central hub for youth activities in town. *scape now consists of areas previously known as the Youth Park, Youth Centre, Skate Park and Field. *scape is the new umbrella brand encompassing the four areas which aims to engage the youths and to facilitate youth development and creative expression. As a new entity, *scape needs to build awareness among its target group of youths – the 15-35 year-olds. Hence, the group was involved to create a new look and feel for *scape’s promotional efforts, and to build awareness of the new *scape, Among the promotional efforts for *scape, three main projects were done – My Space, my Style, my Say Advertising Competition, 100 Chairs project, and *scape’s permanent publicity materials. The My Space, my Style, my Say Advertising Competition was organised to invite youths to have their say on how they want their own youth space to be promoted. 100 Chairs was organised as a signature event for the new *scape promoting arts as a platform for youths to contribute to society and involving a large number of volunteers. *scape permanent publicity materials were created as a consistent fixture in the promotional efforts by *scape. Throughout the whole promotional period, messages about *scape as a place for youths by youths were consistently disseminated, as well as that of *scape as a place for youth development and creative expression. These messages had an impact on the youths, validating the success of the promotional efforts.